The Comparison of Identity Formation Styles in Teenagers with/without Substance Abuse - Frarid Ahmadi; Ebrahim Taghipoor; Anahita Khodabakhshi, K (Drug Control Headquarters, Research and Education Office, 2010)
Aims: The aim of this research was the study of the role of identity formation styles on substance abuse behavior of referred people to addiction withdrawal and DIC centers of Tehran city and its comparison with non addicted people. Method: The research design was causal effect research method, which 100 substance abusers compared with 100 non substance abusers. The sampling method was cluster random sampling and both groups were matched in consideration of age. Bersinesky's identity making questionnaire administered in two samples. Results: The results showed that substance abusers were scored higher on normative and confused/avoidant identity formation also the non substance abusers were scored higher on information identity formation style. Conclusion: With different kind of intervention-training trials the parents and people who are effective on children's identity formation can be mobilized, in order to prevention of identity formation styles which can planning teenagers' substance abusing.